Laughter and Poetry: Five Moments in Central America - Molina Morales, Guillermo (2020)
Five moments of Central American poetry are analyzed thematically, discursively and culturally, as manifestations of the respective ways of representing laughter, as an esthetic option. Its development is analyzed beginning with 19th-century humorous poetry, modernism and its alternatives, sociopolitical poetry, the metaphysical vision with its ironic counterpart, and the novelization of poetry. The conceptual setting underlying the study is the thesis that with Modernity, links between poetry and notions such as beauty or good are broken in favor of an internment in essential aspects of discourse as such and its meaning in the historical setting, as a creative process and as an exercise in reading.